Influence of InxGa1−xAs Underlying Layer on the Structural of the In0.5Ga0.5As Quantum Dots Grown by MOCVD - Didik Aryanto; Zulkafli Othaman; Abdul Khamim Ismail (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2010)
The single layer In0.5Ga0.5As quantum dots (QDs) were grown on a thin InxGa1−xAs underlying layer by metal-organic chemical vapour deposition (MOCVD) via Stranski-Krastanow growth mode. The effect of different indium composition in the In − xGa1−xAs underlying layer was investigated using atomic force microscopy (AFM). AFM images show that the QDs structures were formed on the surface. The dots formation onthe surface changes with different composition of InxGa1−xAs underlying layer. Increasing indium composition in the underlying layer resulted to formation of higher density and smaller size dots. Several large dots were also formed on the surface. Growing of underlying layer reduces the lattice mismatch between In0.5Ga0.5As and GaAs, and decreases the critical thickness of the dots. This strongly influences the dots nucleation on the surface. Growth of quantum dots using underlying layer is one way to modify dot formation in order to achieve uniform QDs of right size and high density, which are essential for QDs device applications.